1995
DOI: 10.1182/blood.v86.7.2699.2699
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the dendritic cell lineage by generating large numbers of Birbeck granule-positive Langerhans cells from human peripheral blood progenitor cells in vitro

Abstract: It is well established by in vivo and in vitro studies that dendritic cells (DCs) originate from hematopoietic progenitor cells. However, the presumed intermediate of Birbeck granule (BG)+ Langerhans cells (LCs) has not been detected in cultures derived from bone marrow or peripheral blood progenitor cells (PBPCs), thus contrasting with the data obtained with cord blood. We show here that large numbers of BG+ LCs can be generated from human CD34+ PBPCs in vitro, when granulocyte-macrophage colony-stimulating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(27 citation statements)
references
References 21 publications
4
22
0
1
Order By: Relevance
“…Large round cells with ruffled uropodia and adherent cells with dendritic appearance were seen. In agreement with previously published data [11,16], FCM analysis indicated that viable cultured cells were distributed into two discrete regions corresponding to large cells with high granularity, and smaller cells with low granularity (data not shown). The large cell region contained as low as 30% and as high as 95% of the cultured cells, but consistently constituted approximately 4% of the total input population.…”
Section: Cytokine-induced Gelatin-adherent Cells Acquired Dc-like Chsupporting
confidence: 92%
See 1 more Smart Citation
“…Large round cells with ruffled uropodia and adherent cells with dendritic appearance were seen. In agreement with previously published data [11,16], FCM analysis indicated that viable cultured cells were distributed into two discrete regions corresponding to large cells with high granularity, and smaller cells with low granularity (data not shown). The large cell region contained as low as 30% and as high as 95% of the cultured cells, but consistently constituted approximately 4% of the total input population.…”
Section: Cytokine-induced Gelatin-adherent Cells Acquired Dc-like Chsupporting
confidence: 92%
“…Since the time they were described [1], dendritic cells (DC) [2] have been under intense investigation because they are thought to induce primary CTL responses [3][4][5][6] and when pulsed with relevant CTL peptide epitopes, regression and elimination of established tumour burden [7][8][9]. A variety of procedures which employ gradients, magnetic beads and/or depletion by immunoglobulin and complement, have been developed in order to obtain purified DC from human peripheral blood, cord blood, or bone marrow CD34 + haematopoietic progenitors [10][11][12][13][14][15]. Human monocytes, following in vitro culture in the presence of GM-CSF and IL-4, also display adhesion molecules and co-stimulatory proteins characteristic of purified dendritic cells [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the self-renewing ability and the multipotentiality of PBPC have been tested in vitro exclusively along those myeloid differentiation pathways through which circulating mature blood cells are generated (namely erythropoiesis, granulo/monocytopoiesis and thrombocytopoiesis). Recently, Mackensen et al (1995) showed that human PBPC generate large number of Birbeck granulepositive Langerhans cells when they are in vitro expanded in liquid culture, in the presence of either tumour necrosis factor or interleukin-4. The above-mentioned culture technique provides a useful model to study in vitro the biological properties of these elements and to generate large numbers of antigen presenting cells for vaccination protocols.…”
Section: Abstract: Circulating Cd34mentioning
confidence: 99%
“…Generation of myeloid DCs in vitro from blood or bone marrow requires the inclusion of granulocyte-macrophage colony-stimulating factor (GM-CSF) in culture (6). Other cytokines supporting myeloid DC production include tumor necrosis factora (TNFa ), interleukin-4 (IL-4), stem cell factor (SCF) and FLT-3 ligand (7). They are high producers of proin ammatory and immunoregulatory cytokines upon stimulation (8).…”
mentioning
confidence: 99%